An Analysis of the Role of the Aisyiyah Organization in Islamic Family Education in Palopo City - Pribadi, Imam; Yusuf, Muhammad; Duriani, Duriani; Anuar, Arman Bin (IAIN PAREPARE, 2025)
Background: Islamic education within the family is the primary foundation in shaping children's character and religious values. Amidst complex social and cultural challenges, women’s organizations such as Aisyiyah hold great potential in supporting family education based on Islamic principles. However, the strategic role of Aisyiyah in this context has not been thoroughly studied, especially at the local level, such as in Palopo City. Research Objectives: This study aims to analyze the role of the Aisyiyah organization in developing Islamic education within families in Palopo City, with a focus on implemented programs, family involvement strategies, and their impact on strengthening Islamic values in household life. Methods: This study employs a qualitative descriptive approach using a phenomenological design. Data collection techniques include observation, in-depth interviews with Aisyiyah administrators and family members, and document analysis. Data were analyzed using the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing with triangulation validation. Results: Findings indicate that Aisyiyah plays an active role in Islamic family education through religious activities, Islamic parenting training, and the empowerment of housewives as primary educators. Formal programs such as TK Bustanul Athfal and non-formal activities such as family religious gatherings help increase collective awareness and create a domino effect within the community. The involvement of both parents, including fathers, signifies the success of Aisyiyah’s inclusive approach. Conclusions: Aisyiyah makes a significant contribution in forming religious and resilient families through a community-based Islamic education approach. The practical implications of this study highlight the importance of synergy between religious organizations and educational institutions in reinforcing family spiritual resilience. Further research is recommended to explore replication models in other regions and to adopt quantitative approaches for broader impact measurement.